2015
DOI: 10.1111/aos.12763
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological findings in relation to auxological data in moderate‐to‐late preterm preschool children

Abstract: ABSTRACT.Purpose: To evaluate ophthalmological findings in preschool children born moderate-to-late preterm (MLP) and relate the findings to auxological data at birth and at 5.5 years of age. Methods: Seventy-eight MLP children [gestational age (GA) 32-36 weeks; 34 girls; mean age 5.7 years] were investigated. Gestational age, weight, length and head circumference at birth and at the time of assessment were registered. Visual acuity (VA), refraction, orthoptic evaluation, slit-lamp examination and ophthalmosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…This is in fair agreement with our previous results on the same cohort investigated at age of five years old (Raffa et al. ) and with Robaei's study where moderate prematurity was not associated with increased risk for myopia or significant hyperopia (Robaei et al. ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in fair agreement with our previous results on the same cohort investigated at age of five years old (Raffa et al. ) and with Robaei's study where moderate prematurity was not associated with increased risk for myopia or significant hyperopia (Robaei et al. ).…”
Section: Discussionsupporting
confidence: 94%
“…; Raffa et al. ). At 8 years of age, 50 children (29 boys, 21 girls) with a mean ± standard deviation (SD) GA of 35 ± 1.5 weeks and birthweight (BW) of 2299 ± 469 grams of the original neonatal study ( n = 247) and the substudy at 5.5 years of age ( n = 78) agreed, with their guardians' permission, to take part in this study.…”
Section: Methodsmentioning
confidence: 98%
“…The impact on eye development partially depends on the extent of prematurity but is linked to other factors, including oxygen, inflammation, or nutrition strategies (Casteels et al, ; Hellstrom et al, ; O'Connor et al, ). However, subtle differences have also been documented for late preterm neonates compared with term neonates, suggesting a continuum of impact (Raffa et al, , ). These findings in preterms should be taken into account when selecting animal experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…4 The results of a few studies have also revealed increased ocular morbidity in infants born moderately preterm (MP) (32 + 0/7-33 + 6/7 weeks) and late preterm (LP) (34 + 0/7-36 + 6/7 weeks). 5,6 The incidence of congenital hearing impairment has been estimated to be 1 to 2 per 1000 newborns, and, in risk populations, the incidence has been reported to be increased 10-to 50-fold. 7,8 VP birth, admission to a NICU, and low birth weight have been reported to increase the risk of hearing disabilities in childhood.…”
mentioning
confidence: 99%